2015
DOI: 10.18488/journal.1/2015.5.11/1.11.656.677
|View full text |Cite
|
Sign up to set email alerts
|

Task Difficulty of Macro-Genres and Reading Strategies and Reading Comprehension

Abstract: Contribution/ OriginalityThis study is one of very few studies which have investigated the correlation between task difficulty of the four macro-genres (i.e., descriptive, narrative, argumentative, expository) and 657learners' reading comprehension and their use of reading strategies in the same macro-genres. The results can be utilized by language researchers and practitioners.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Other studies (e.g., Ahmadi & Mansoordehghan, 2012;Sotoudenamah & Asadian, 2011;Bugel & Buunk, 1996;Samadi & Maghsoudi, 2013), in contrast, reported that male learners were better in the reading compression than the female ones. and Rouhi, Jafarigohar, Alavi, and Hosseini (2015), however, showed that there were no significant difference observed between males and females in their reading comprehension in the four major types of macro-genres (i.e., the descriptive, narrative, argumentative, and expository). The performance of males and females in the reading comprehension in the four types of macro-genres (i.e., descriptive, narrative, argumentative, and expository) is supposed to be an issue of interest in language teaching which may shed some light on the gender-related performance of the L2 learners and practitioners.…”
mentioning
confidence: 80%
“…Other studies (e.g., Ahmadi & Mansoordehghan, 2012;Sotoudenamah & Asadian, 2011;Bugel & Buunk, 1996;Samadi & Maghsoudi, 2013), in contrast, reported that male learners were better in the reading compression than the female ones. and Rouhi, Jafarigohar, Alavi, and Hosseini (2015), however, showed that there were no significant difference observed between males and females in their reading comprehension in the four major types of macro-genres (i.e., the descriptive, narrative, argumentative, and expository). The performance of males and females in the reading comprehension in the four types of macro-genres (i.e., descriptive, narrative, argumentative, and expository) is supposed to be an issue of interest in language teaching which may shed some light on the gender-related performance of the L2 learners and practitioners.…”
mentioning
confidence: 80%
“…Therefore, the present study aims to investigate whether and how WM interacts with strategy use in the process of L2 reading comprehension. Additionally, the present study also examines whether task difficulty plays a role in this process, as strategy use might vary according to task variables (e.g., Oxford, Cho, Leung, & Kim, 2004;Rouhi, Jafarigohar, Alavi, & Asgarabadi, 2015). By including these variables simultaneously in one design, the current study intends to enhance our knowledge of the precise mechanism by which WM functions in L2 reading.…”
Section: Introductionmentioning
confidence: 99%